Efek pemberian susu protein tinggi dan tingkat kepatuhan terhadap kenaikan berat badan badan dan status gizi anak usia 15-17 tahun - Fauziah Fauziah; Clara Meliyanti Kusharto; Budi Setiawan (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2022)
High-protein milk is a nutrient-dense food with potential bioactive compounds that are thought to affect intake quality to weight gain and improvement of nutritional status. The study aimed to analyze the effect of high protein milk intervention on energy and macronutrient intake, weight gain, nutritional status, and the relationship between the level of product consumption compliance with weight gain and nutritional status. This study is a Randomized Control Trial (RCT). Subjects were divided into two groups: the treatment group (high protein milk and nutrition education intervention) and the control group (nutrition education intervention). The results showed a significant increase in energy and protein intake in the treatment group (p> 0,05) compared to the control group. The weight of the treatment group increased significantly (p=0,008; 3,93±2,78kg) compared to the control group. The BMI of the treatment group increased significantly after 90 days of intervention (p= 0,000; 0,74±0.54kg/m2). The level of compliance of the subjects included in the high category (>70%). Still, there was no correlation between the level of adherence to high milk consumption with weight gain and subject status. In conclusion, high protein milk can increase energy and protein intake, affecting weight gain and improvement in children aged 15-17 years.